Towards a Kenyan legal and ethical framework on surrogacy - Lumbasyo, Robai Ayieta (My University, 2015)
Surrogacy motherhood, an arrangement involving one woman gestating a baby to be raised by another, is still a relatively ‘new’ technology in Kenya seeing as the first surrogate birth in Kenya happened in August 2007. Being a new technology therefore, the practice is still stifled in uncertainty thereby raising a complex web of legal and ethical issues. The fact that there is no legal and ethical framework to regulate surrogacy arrangements in Kenya, exposes the practice to corruption and other exploitative activities. Lapses and lacuna in the legal framework makes it hard to standardize the practice of surrogacy in Kenya, leaving the consumers of the service (technology) at the mercy of personal interpretation of the service providers. It is therefore essential that a legal and ethical framework is formulated to not only curb the rising incidences of exploitation but to also safeguard the interests of all parties involved. It is under this background that I intend to normatively assess the current practices of surrogacy in Kenya and make recommendations based on best practices internationally to guide the development of a legal and ethical framework on surrogacy in Kenya.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree Master of Science in Medicine Bioethics and Health Law, May 2015, Johannesburg
Keywords: Kenya; Surrogate mothers